Desire for labor companionship and its associated factors among pregnant women attending antenatal care at public health facilities in Debre Berhan City: a cross-sectional study - Silesh, Mulualem; Demisse, Tesfanesh Lemma; Abebe, Kidist Ayalew; Taye, Birhan Tsegaw; Moltot, Tebabere; Chekole, Moges Sisay; Kasahun, Fetene; Mekuriyaw, Abebayehu Melesew; Kebede, Tirusew Nigussie; Hailemeskel, Kibret (Frontiers in Global Women's Health, 2025)
BackgroundAllowing women to have a companion of their choice during labor and delivery is a cost-effective strategy to enhance the quality of maternal care and promote a positive birth experience. Due to the limited studies on women's preferences for labour companionship, this study aimed to assess the desire for labour companionship and its associated factors among pregnant women attending ante-natal care at public health facilities in Debre Berhan City.MethodA facility-based cross-sectional study was conducted from August 1–30, 2022. A face-to-face questionnaire administered was used to collect data. Then, entered into Epi-Data version 4.6 and exported to SPSS version 25 for data analysis. In multivariable logistic regression analysis, variables with P < 0.05 with AOR and 95% CI were considered statistically significant.ResultOf 408 participants, 68.6% [95% CI: 63.8, 73.9] of pregnant women desired to have companionship in labour. Women who were living in urban [AOR: 2.32; 95% CI: 1.336, 4.022], had secondary level of education [AOR: 0.39; 95% CI: 0.207, 0.726], being pregnant for the first time [AOR: 1.88; 95% CI: 1.197, 2.945], women who had a good knowledge towards labour companion [AOR: 2.4; 95% CI: 1.522, 3.797] were statistically significant with desire on labour companionship.ConclusionThe magnitude of desire towards labour companionship in this study area was found high. Place of residence, educational attainment, number of pregnancies (gravidity), and level of knowledge about labour companions significantly contribute to women's desire for labour companionship. Therefore, to increase the desire for labor companions; antenatal education about its benefits should emphasized, particularly in rural areas and among less-educated communities. Providing tailored support for primigravida women and underserved populations can also help to integrate labor companionship into maternal care.